2014
DOI: 10.1586/14760584.2014.944901
|View full text |Cite
|
Sign up to set email alerts
|

Importance of (antibody-dependent) complement-mediated serum killing in protection againstBordetella pertussis

Abstract: Pertussis is a highly contagious respiratory disease that is caused by Bordetella pertussis. Despite being vaccine preventable, pertussis rates have been rising steadily over the last decades, even in areas with high vaccine uptake. Recently, experiments with infant baboons indicated that although vaccination with acellular pertussis vaccines prevented disease, no apparent effect was observed on infection and transmission. One explanation may be that current acellular pertussis vaccines do not induce high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 125 publications
(137 reference statements)
0
8
0
1
Order By: Relevance
“…With respect to the antibody responses to these antigens, these were found to resemble antibody responses to natural B. pertussis infection in humans 29,30 and mice 16 . These broad antibody responses induced by omvPV may provide protection through multiple antibody mechanisms such as opsonizing and bactericidal activity as well as prevention of bacterial adhesion 31,32 . However, the functionality of omvPV-induced IgG and IgA antibodies remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the antibody responses to these antigens, these were found to resemble antibody responses to natural B. pertussis infection in humans 29,30 and mice 16 . These broad antibody responses induced by omvPV may provide protection through multiple antibody mechanisms such as opsonizing and bactericidal activity as well as prevention of bacterial adhesion 31,32 . However, the functionality of omvPV-induced IgG and IgA antibodies remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data point to a potentially critical role of complement in protection following various clinically approved vaccines (Frasch et al, 2009; Geurtsen et al, 2014) as well as experimental vaccines (McCoy et al, 2013), pointing to a role for vaccine-induced antibody-driven complement deposition as a potentially key predictor of immunity. While various assays have been developed to measure complement activity in human plasma, a sample-sparing, high-throughput assay could provide critical value for the evaluation and dissection of complement-activating antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that B. pertussis has developed strategies for immune evasion, including the ability to bind complement-regulatory proteins (Barnes and Weiss, 2001;Berggård et al, 2001;Amdahl et al, 2011;Marr et al, 2011;Geurtsen et al, 2014;Hovingh et al, 2017). The two Bvgactivated autotransporter proteins Vag8 and BrkA are known to be involved in complement resistance by binding C1 esterase inhibitor (C1-INH) (Marr et al, 2011) or preventing the deposition of C3 onto the bacteria and the formation of the membrane attack complex (Barnes and Weiss, 2001).…”
Section: Introductionmentioning
confidence: 99%